The Evolution of Diplomatic Immunity: A Jurisprudential Analysis - ODOK, Joseph Abang; NABIEBU , Miebaka (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The concept of diplomatic immunity has evolved over centuries as an essential element of international relations, safeguarding diplomats and envoys to facilitate peaceful interactions between states. This research explores the historical development of diplomatic immunity, from its rudimentary beginnings in ancient civilizations to its formal codification in modern international law. Early customs and legal frameworks, such as those found in the Institutes of Manu, Homeric poetry, and Kutilya’s Arthashastra, laid the groundwork for diplomatic protection, reflecting the need to secure envoys in their duties. The study also examines the transformation of the roles and responsibilities of diplomats, from messengers to negotiators, and how the legal foundation for their immunity adapted accordingly. The codification of diplomatic immunity in the Vienna Convention on Diplomatic Relations of 1961 marked a turning point, establishing a comprehensive framework that governs diplomatic privileges and immunities. Despite its critical role in promoting international diplomacy, diplomatic immunity remains a subject of debate, particularly regarding its potential for misuse and the ongoing need to balance state sovereignty with diplomatic protections. This research provides a comprehensive understanding of the evolution, legal framework, and contemporary relevance of diplomatic immunity in international law.